FUNCTIONAL OUTCOME OF ARTHROSCOPIC ASSISTED MINI OPEN ROTATOR CUFF TEAR REPAIR - Kapil Ghorpade; Patil, Jaydeep; Patil, Tanish; Khambalkar, Shouryashil (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to analyze the functional outcome of patients with rotator cuff injuries treated by arthroscopically-assisted mini-open repair. Methods: This was a prospective and cohort study conducted in the Department of Orthopaedics of Prakash Institute of Medical Sciences (PIMS) and Research, Urun Islampur Dist Sangli. Forty patients with rotator cuff injuries treated by arthroscopic assisted mini open rotator cuff tear repair were included in this study on the basis of a predefined inclusion and exclusion criteria. Post-surgery patients were followed up for 6 months. At each follow-up visit, functional outcome was assessed by Constant Score (CS) and University of California-Los Angeles (UCLA) shoulder scale. For statistical purpose, SSPS 21.0 software was used and p<0.05 was taken as statistically significant. Results: A total of 40 patients were included in this study out of which there were 23 (57.50 %) males and 17 (42.50 %) females with a M:F ratio of 1:0.73. The mean age of affected patients was found to be 57.07±11.31years. The most common cause of rotator cuff tear was degenerative changes which was seen in 19 (47.50%) patients followed by spontaneous rotator cuff tear (30.00%) and traumatic rotator cuff injury (22.50%). There was significant functional improvement from pre-operative to last follow-up period as shown by improved CS and UCLA scores (p<0.05). Conclusion: Arthroscopic assisted mini-open surgery for rotator cuff injuries is found to have excellent results in terms of functional outcome.